2014
DOI: 10.1155/2014/273129
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of a Lipid-Based Preparation fromMycobacterium smegmatisin a Murine Model of Progressive Pulmonary Tuberculosis

Abstract: A more effective vaccine against tuberculosis (TB) is urgently needed. Based on its high genetic homology with Mycobacterium tuberculosis (Mtb), the nonpathogenic mycobacteria, Mycobacterium smegmatis (Ms), could be an attractive source of potential antigens to be included in such a vaccine. We evaluated the capability of lipid-based preparations obtained from Ms to provide a protective response in Balb/c mice after challenge with Mtb H37Rv strain. The intratracheal model of progressive pulmonary TB was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…17 Lipds are important potential targets for vaccine development against TB considering the importance of these components in the virulence of Mtb. 37,39 Several vaccine candidates containing mycobacterial lipids have demonstrated protective capacity in guinea pigs and mice [40][41][42][43] The current study suggests that PLBCG-Al as a booster to BCG could be a new alternative candidate to be tested for protection against TB in further phases of evaluation.…”
Section: Resultsmentioning
confidence: 98%
“…17 Lipds are important potential targets for vaccine development against TB considering the importance of these components in the virulence of Mtb. 37,39 Several vaccine candidates containing mycobacterial lipids have demonstrated protective capacity in guinea pigs and mice [40][41][42][43] The current study suggests that PLBCG-Al as a booster to BCG could be a new alternative candidate to be tested for protection against TB in further phases of evaluation.…”
Section: Resultsmentioning
confidence: 98%
“…The immunization with these proteins emulsified with IFA induced the secretion of protective Th1 cytokine (IFN-γ) from spleen cells and also lowered the bacterial load significantly in lungs [40]. Alum salts are known to be Th2-inducing adjuvants, however due to their safety and function of increasing the stability and immunogenicity of recombinant proteins, they have been widely used in pursuit of developing subunit TB vaccines and to compare new adjuvants [41][42][43][44][45]. Despite the positive correlation between the induction of high Th1 responses and protection against TB in mice, it has been shown that the use of Th2 inducing adjuvants, such as Alum, is not associated with harmful effects [46].…”
Section: Discussionmentioning
confidence: 99%
“…Although total lipid-based liposomes induced CD1 restricted T-cell responses and demonstrated an improved pulmonary pathology ( 39 , 40 ), the specific lipid component among the total lipids that was responsible for the pathological protection was not clear. Recently, a diacylated sulfoglycolipids (Ac 2 SGL) and phosphatidylinositol mannoside 2 (PIM 2 )-loaded liposome vaccine induced protective immune responses in guinea pigs ( 41 ), but the adjuvant effect of PIM 2 and trehalose-6,6-dibehenate (TDB), a component of the liposomal nanocarrier ( 42 , 43 ), may complicate the bacterial and pathological protection observed.…”
Section: Discussionmentioning
confidence: 99%